Geoclimatic determinism as the methodological basis of geopolitics - Novikau, Uladzimir T.; Novikava, Volha U. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The issue reveals how the geography and climat influence the social history and political relations such as the state politics. Therefore the authors pay attention to the potentiality to overemphasize this influence what is the basis of geoclimatic determinism theory. Main periods in the history of philosophy concerned with the influence of geoclimatic factor on sociodynamics are taken under consideration, philosophical and scientific views of Aristotle, Abu Nasr al-Farabi, Ibn Khaldun, J. Bodin, Ch. L. Montesquieu, J.-F. de Saint Lambert, J. J. Rousseau are analyzed such as conceptions of H. T. Bukle, German geographers and economists K. Ritter, W. Christaller, A. Lösch, F. Naumann, F. Ratzel, A. Hettner. Special attention is paid on the ways of this theme investigation by Russian philosophers and scientists N. A. Berdyaev, A. A. Bogdanov, V. O. Kluchevsky, P. P. Semyonov-Tan-Shansky, L. I. Mechnikov, Eurasianists and by geographer V. V. Klimenko, who worked up the comparative chronology of main facts in climatic and social history by last five thousand years.
Keywords: philosophy; methodology; geopolitics; human; nature; terrain; climat; state; territory; population